Mapping Russia’s Global Influence - Grzegorz Ptaszek; Bohdan Yuskiv; Piotr Bajor (Politeja, 2025)
The article presents a comprehensive analysis of Russia’s strategic goals and instruments of influence in foreign policy between 2014 and 2021 for implementing global ambitions. Using cluster and index analysis methods, the study identifies eleven regions of influence (ROIs) and four main clusters: Border Security (BS), Economic-Historical Ties (EHT), Eastern Markets (EM), and Dialogue with North America (DNA). The analysis showed that Russia’s activity in certain regions was differentiated and adapted to their strategic importance. The highest activity indicators were recorded in Central and Southern Africa, the Western Balkans, and the Baltic States, where Russia used various instruments of influence—from political to economic to informational. The study confirms that Russian foreign policy after 2014 was aimed at undermining Western dominance and building a multipolar world. The findings reveal Russia’s systematic and differentiated approach to achieving strategic goals in different regions of the world and contribute to a better understanding of its role in shaping the contemporary international order.